Opening up Corpus FinSL: enriching corpus analysis with linguistic ethnography in a study of constructed action - Puupponen Anna; Hodge Gabrielle; Anible Benjamin; Salonen Juhana; Wainio Tuija; Keränen Jarkko; Hernández Doris; Jantunen Tommi (Linguistics)
Corpus methods are now established within the field of signed language linguistics. Empirical investigations of signed language corpora have challenged many early assumptions about the nature of deaf community signed languages, while making us more aware of the limitations of traditional corpus documentation methods. One limitation relates to insufficient documentation of ethnographic information that is often necessary for accurately understanding and interpreting corpus data. Linguistic ethnography offers unique possibilities for addressing this limitation. This article outlines a novel interview method developed to enrich the original Corpus of Finnish Sign Language (Corpus FinSL) with additional ethnographic information eight years after it was first documented and archived with standard IMDI corpus metadata. We interviewed 22 Corpus FinSL signers about their family and social networks, as well as their lifelong language, geographical, educational, and employment trajectories. Here we describe how this information illuminates the linguistic analysis and interpretation of constructed action – an enactment-based way to express meaning – in Corpus FinSL data. Our results reveal constructed action in FinSL discourse is influenced by factors like signer’s educational background and age, but not exclusively by family networks or use of other sign languages. The interview materials demonstrate diversity and change in the communicative ecologies of FinSL, which is discussed in relation to the use of constructed action in FinSL. We argue that this kind of approach enables signed language corpus linguistics to “open up” more to signers’ lived experiences, while still “tying down” empirical descriptions of FinSL. A major benefit is the enrichment of both machine-readable annotations and metadata, while supporting deeper engagement between deaf signing communities and signed language corpus projects.